Confluence effect of debris-filled damage and temperature variations on guided-wave ultrasonic testing (GWUT) - Olisa, Samuel C.; Khan, Muhammad A. (MDPI, 2024)
Continuous monitoring of structural health is essential for the timely detection of damage and avoidance of structural failure. Guided-wave ultrasonic testing (GWUT) assesses structural damages by correlating its sensitive features with the damage parameter of interest. However, few or no studies have been performed on the detection and influence of debris-filled damage on GWUT under environmental conditions. This paper used the pitch–catch technique of GWUT, signal cross-correlation, statistical root mean square (RMS) and root mean square deviation (RMSD) to study the combined influence of varying debris-filled damage percentages and temperatures on damage detection. Through experimental result analysis, a predictive model with an R2 of about 78% and RMSE values of about 7.5×10^−5 was established. When validated, the model proved effective, with a comparable relative error of less than 10%.
Keywords: ultrasonic; guided wave; RMS; damage detection